2017
DOI: 10.1177/014556131709600702
|View full text |Cite
|
Sign up to set email alerts
|

Post-Tonsillectomy Hemorrhage Rates in Children Compared by Surgical Technique

Abstract: Postoperative chylous fistula after neck dissection is an uncommon complication associated with Significant patient morbidity. Octreotide acetate is a somatostatin analogue established in the treatment of chylothorax; however, its utility in the management of cervical chylous fistulae has not been fully evaluated. The investigators hypothesized that chylous fistula can be managed by a combination of octreotide and peripheral totalparenteral nutrition (TPN). A retrospective review of cases compiled at our insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 20 publications
(23 reference statements)
3
24
1
6
Order By: Relevance
“…The results showed that eight (80%) of 10 patients in low‐output group and four (25%) of 16 patients in high‐output group got resolution of chyle fistula by octreotide therapy in combination with other conservative management. However, the overall success rate of conservative therapy was 46.2% (12/26), which was considerably lower than that described in previous studies (reported range, 80%‐100%) . This may have been due to the high‐output cases with a higher proportion in this study.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…The results showed that eight (80%) of 10 patients in low‐output group and four (25%) of 16 patients in high‐output group got resolution of chyle fistula by octreotide therapy in combination with other conservative management. However, the overall success rate of conservative therapy was 46.2% (12/26), which was considerably lower than that described in previous studies (reported range, 80%‐100%) . This may have been due to the high‐output cases with a higher proportion in this study.…”
Section: Discussioncontrasting
confidence: 79%
“…This may have been due to the high‐output cases with a higher proportion in this study. Sixty‐two percent of patients (16/26) had high‐output chyle fistula (>500 mL), while the proportion of high‐output cases in previous studies was 33.3% (4/12), 21.1% (4/19), and 20.0% (2/10), respectively . Therefore, our findings in the present study suggest that octreotide therapy may have a limited effect on high‐output leakage.…”
Section: Discussionsupporting
confidence: 42%
“…In the article of Sheybani et al, Lipiodol embolization to the brain and to the lung was reported as a CL-related major complication after intranodal CL, and the patient died 69 days after CL (because all supportive care was withdrawn due to a very low probability of meaningful recovery after a complicated clinical course including deteriorating mental status and pneumonia) [29]. Somatostatin is secreted from the pancreas, stomach, and duodenum, and it exerts inhibitory actions on stomach acid and bile secretion, and thus reduces chyle flow by suppressing the absorption of fat, which is the raw material for chyle [47]. This document was downloaded for personal use only.…”
Section: Technical Aspects Of CLmentioning
confidence: 99%
“…Bu çalışmada oktreotidin hem yüksek hem düşük akımlı ŞF'lerde açık bir tedavi etkisi olduğu ve hastanede yatış sürelerini ve morbiditeyi azalttığı görülüyor. Literatürde çalışmamız dışında oktretidin başlangıç tedavisi olarak konservatif tedavide kullanıldığı sadece iki çalışma vardır fakat vaka sayıları çalışmamıza kıyasla nispeten azdır 13,18 . Chan ve arkadaşlarının çalışmasında 13 Oktreotid verilme dozu, yolu ve süresi de çalışmalarda değişkenlik göstermektedir.…”
Section: Gereç Ve Yöntemunclassified
“…Bildiğimiz kadarıyla çalışmamız literatürde oktreotid tedavisinin ŞF tedavisinde etkinliğini değerlendiren çalışmalar içinde en fazla hasta sayısı bulunan çalışmadır. 12,13,18,19 . Oktreotidin ŞF tedavisinde etki mekanizmasının gastrointestinal ve pankreatik salgıları azaltması, hepatik venöz basıncı düşürmesi, splankik kan akımını azaltması sonucu olduğu düşünülmektedir 20 .…”
unclassified